Value of severe liver iron overload for assessing heart iron levels in thalassemia major patients. Issue 4 (31st March 2016) - Chen, Xiaodong; Zhang, Hui; Yang, Qihua; Luo, Zebin; Zhang, Zuoquan; Cheng, Ziliang; Mao, Jiaji; Chan, Queenie; Xu, Honggui; Liang, Biling; Guo, Hua
Abstract : Purpose: The relationship between severe liver iron overload (LIO) and heart iron overload (HIO) in transfusion‐dependent patients with thalassemia major (TM) is uncertain. Whether severe LIO can serve as an index for assessing heart iron deposition has vital clinical significance. Therefore, our aim is to determine if a close relationship exists between severe LIO and HIO. Materials and Methods: We examined 110 TM patients who underwent T2* measurement in the liver and heart on a 1.5 Tesla MRI scanner. Various statistical analysis methods were used to assess the relationship. Results: Most of these patients suffered from severe LIO (58.18%, liver T2* < 1.4 ms). Both Pearson's and Spearman's tests showed a significant correlation between liver T2* and heart T2* values (with a correlation coefficient of 0.408 and 0.550, respectively, both P < 0.0001). A nonlinear model, with the equation of Heart T2* = 37.974–17.684 / Liver T2*, was found to be the best model to indicate the relationship between liver T2* and heart T2*. Receiver operating characteristic (ROC) analysis showed the area under the ROC curve of liver T2* and serum ferritin for predicting HIO was 0.812 (95% confidence interval [CI]: 0.731–0.892; P < 0.0001) and 0.69 (95% CI: 0.585–0.795; P = 0.001), respectively. Conclusion: Our preliminary data suggest the existence of a close relationship between severe LIO and HIO. High liver iron levels appear to increase the risk of heart iron deposition. This further supports the concept of critical liver iron concentration, above which elevated heart iron is present. J. MAGN. RESON. IMAGING 2016;44:880–889.